Photodegradation of phenol over flame-made Sn-doped ZnO nanoparticles - Wetchakun K. (2014)
Undoped ZnO and 0.5-5.0 at.% Sn-doped ZnO nanoparticles were synthesized by flame spray pyrolysis (FSP) using zinc naphthenate and tin (II) 2-ethylhexanoate dissolved in xylene as the precursors under a 5/5 (precursor/oxygen) flame condition. UV-Vis absorption characteristics of the samples were investigated for understanding and relating with the physiochemical characteristics in photocatalytic applications. Kinetic analyzes indicated that the photodegradation rates of phenol could be approximated as pseudo-first-order and zero-order kinetics in the case of undoped ZnO and Sn-doped ZnO nanoparticles respectively, according to the Langmuir- Hinshelwood model. The effect of Sn doping revealed the deterioration of the phenol photodegradation performance over ZnO-based catalysts, possibly due to the formation of a deep state in the ZnO band gap energy. © (2011) Trans Tech Publications, Switzerland.